Liberalisation of capital controls: A review of South African exchange controls and their impact on exchange rate stability - Ndemera, Tendai (Research of GSB, 2018)
The 2007/08 global financial crisis, including pre- and post-crisis reform, led economies to reexamine the concept of capital controls. Theoretical and empirical literature has been divided regarding their effectiveness. This research paper assesses the impact of capital controls on exchange rate stability in South Africa (particularly exchange restrictions used to insulate economies from excessive currency volatility) using time-series analysis and employs event study methodology (Kothari & Warner, 2006; MacKinlay, 1997) to measure the impact of the capital control actions. More specifically, this research paper evaluates the impact of capital controls on (a) exchange rate returns, (b) volatility and (c) liquidity in South Africa for the period commencing 1 January 1999 to 31 December 2014 including the period during the 2007/08 financial crisis. The research paper applies methodology from empirical research on capital controls and currency stability (Pandey, Pasricha, Patnaik, & Shah, 2015), volatility using standard deviation and the GARCH (1,1) model (Abdalla, 2012; Bollerslev, 1986; Farrell, 2001) and liquidity (Karnaukh, Ranaldo, & Söderlind, 2015). In addition, it attempts to determine the effect on exchange rate movements directly attributable to capital controls i.e., the local factors, by removing the dollar risk factor that constitute a significant portion of exchange rate time series as noted by Verdelhan (2015), which serves as the base model for the event study. The research paper finds that overall the key capital controls selected do not have a significant impact on the ZAR/USD exchange rate with limited evidence of an effect on returns, volatility and liquidity.